MEMBENTUK GENERASI CINTA LAUT MELALUI PENDIDIKAN OCEAN LITERACY BAGI SISWA SEKOLAH DASAR DI DESA JEROWARU, LOMBOK TIMUR (Jurnal Pepadu, 2023)
The ocean is a natural resource with abundant potential, encompassing both marine biodiversity and valuable minerals such as oil, gas, and metals. However, this potential is currently facing serious challenges due to overexploitation and environmental degradation. Overfishing, pollution, and uncontrolled coastal development have threatened fish populations and marine ecosystems. Additionally, the phenomenon of climate change has increased pressure on ocean resources. Serious efforts are needed to curb and address the rate of ocean resource degradation, and one of them is by enhancing ocean literacy. This community engagement activity aims to enhance ocean literacy among the community, especially elementary school students in the Jerowaru District, East Lombok Regency. Various forms of activities and media that are used to convey ocean literacy content in this community engagement, i.e. drawing workshop, watching videos, retelling watched videos, and storytelling. Based on the conducted community engagement activities, it is evident that the enthusiasm of elementary school students in participating is very high. The students enthusiastically followed all the activities, executed all instructions well, and were able to provide feedback by answering questions about ocean literacy materials accurately and effectively.
Keywords: ocean literacy, elementary student, enthusiasm